A formação e o início da estruturação urbana de Catanduva - SP - Rosa, Larissa de Fátima [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This work addresses the municipality of Catanduva (São Paulo) from its foundation as a religious heritage site to the structuring of its urban fabric following the installation of the Araraquara Railway (EFA) in 1910. Originally established to transport the region’s coffee production, the railway also fostered the city’s growth by boosting its economy, driving modernization, and influencing its urban layout. This research aims to study the genesis of the municipality of Catanduva, located in the rural areas of Araraquara, from the 19th century until the end of the First Brazilian Republic (1930). Within this context, the study analyzes how the EFA functioned as a structuring element of the city and seeks to understand issues such as the first land settlers in the region, the initial urban layout, the urban infrastructure introduced through the railway’s implementation, and how the actions of the local political elites (the "coronéis") influenced this broader scenario. The methodology adopted is a case study grounded in historical procedures and a historical-interpretative approach, combined with qualitative methods, encompassing specific techniques for both data collection and analysis. This is, therefore, an in-depth study supported by exploratory field research and a detailed narrative review. Additionally, the study includes bibliographic and documentary research, drawing from journalistic archives, notarial, cartographic and iconographic records, legislation, as well as documents and reports related to the EFA, accompanied by a critical analysis of the information obtained.

Este trabalho trata do município de Catanduva (SP) a partir de sua fundação como patrimônio religioso, da estruturação de sua malha urbana com a instalação da Estrada de Ferro Araraquara (EFA), em 1910. Instalada com a finalidade de escoar a produção cafeeira da região, a ferrovia também impulsionou o crescimento da cidade, dinamizando sua economia, trazendo modernização e influenciando no seu traçado urbano. Por meio dessa pesquisa, pretende-se estudar a gênese do município de Catanduva situada nos campos de Araraquara, do século XIX até o final da Primeira República (1930). Nesse contexto, será analisado de que forma a EFA agiu como elemento estruturador da cidade e compreender questões como os primeiros posseiros de terras dessa região, o primeiro traçado urbano, através da implantação dos trilhos analisar os elementos de infraestrutura urbana trazidos pela ferrovia e também como a atuação dos coronéis influenciou nesse panorama geral. A metodologia adotada é o estudo de caso compondo o procedimento histórico, a pesquisa histórica-interpretativa, associada à abordagem qualitativa, envolve métodos e técnicas específicas tanto para a coleta quanto para a análise de dados. Trata-se, portanto, de um estudo aprofundado, que se apoia em uma investigação de campo exploratória e em uma revisão narrativa detalhada. E, ademais, foi utilizado levantamento bibliográfico, levantamento documental (arquivos jornalísticos, arquivos cartoriais, cartográficos e iconográficos, legislações, além dos documentos e relatórios sobre a EFA e a análise crítica das informações obtidas.
The formation and beginning of the urban structuring of Catanduva - SP
Keywords: Formação urbana; História urbana; Morfologia urbana; Patrimônio religioso; Urbanização; Urban formation; Urban history; Urban morphology; Religious heritage; Urbanization